Batch study and experimental design for the removal of reactive orange 16 from aqueous solution using chitosan beads - Tong, Jin Ying (2024)
Dye contamination of wastewater poses serious risks to the environment and has detrimental effects on the human health as well. In this research, the feasibility of using chitosan beads as promising adsorbent for the removal of Reactive Orange 16 was studied. Several factors such as contact time, initial concentration of dye, adsorbent dosage, agitation rate and pH were included in batch adsorption studies to examine their impact towards the adsorption process. The characterization study on the synthesized chitosan beads was carried out using Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) spectroscopy, Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). The equilibrium adsorption data was found to be best fitted to both Langmuir and BET isotherm model with R2 value of 0.9940 and maximum adsorption capacity of 38.17 mg/g. Besides, the adsorption of RO16 by chitosan beads followed the pseudo-second order kinetic model. Modification on the chitosan beads was performed by adding polyethylene glycol (PEG) to evaluate its adsorption performance. Plackett-Burman design was used to identify the significant factors in the adsorption process whereas RSM was utilized for the optimization study. The percentage uptake of RO16 can achieve up to 94.55% under optimum conditions of pH 3, 360 minutes of contact time, initial dye concentration of 100 mg/L, adsorbent dosage of 0.05 g and agitation rate of 150 rpm.